3D simulations of strongly magnetized non-rotating supernovae: explosion dynamics and remnant properties. Issue 3 (11th November 2022) - Varma, Vishnu; Müller, Bernhard; Schneider, Fabian R N
ABSTRACT: We investigate the impact of strong initial magnetic fields in core-collapse supernovae of non-rotating progenitors by simulating the collapse and explosion of a 16.9 M_ star for a strong- and weak-field case assuming a twisted-torus field with initial central field strengths of ≈ 10^12 and ≈ 10^6 G . The strong-field model has been set up with a view to the fossil-field scenario for magnetar formation and emulates a pre-collapse field configuration that may occur in massive stars formed by a merger. This model undergoes shock revival already 100 ms after bounce and reaches an explosion energy of 9.3× 10^50 erg at 310 ms, in contrast to a more delayed and less energetic explosion in the weak-field model. The strong magnetic fields help trigger a neutrino-driven explosion early on, which results in a rapid rise and saturation of the explosion energy. Dynamically, the strong initial field leads to a fast build-up of magnetic fields in the gain region to 40 per cent of kinetic equipartition and also creates sizable pre-shock ram pressure perturbations that are known to be conducive to asymmetric shock expansion. For the strong-field model, we find an extrapolated neutron star kick of ≈ 350 km s^-1, a spin period of ≈ 70 ms, and no spin-kick alignment. The dipole field strength of the proto-neutron star is 2× 10^14 G by the end of the simulation with a declining trend. Surprisingly, the surface dipole field in the weak-field model is stronger, which argues against a straightforward connection between pre-collapse fields and the birth magnetic fields of neutron stars.